Perjanjian Kerjasama Jual Beli melalui Sistem E-commerce dengan Asas Itikad Baik Berdasarkan Undang-Undang No. 7 tahun 2014 Tentang Perdagangan cq PP RI No. 80 Tahun 2019 Tentang Perdagangan Melalui Sistem Elektronik - Noviriska; Dwi Atmoko (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The principle of good faith means that agreements made must be carried out with due regard to the norms of propriety and morality. In a buying and selling transaction, there is an obligation that must be fulfilled by the parties not to do anything that does not make sense, that is, does not conflict with the norms of propriety and decency, with the hope of creating justice for the parties and not causing harm to either party. party. Buyers of goods in good faith or otherwise, as opposed to people in bad faith, are in good faith with subjective anarchy. A buyer of goods in good faith is a person who buys goods with full confidence that the seller really owns the goods purchased. He doesn't know at all, if he bought from an unauthorized person, why he would be called an honest buyer, in this case in good faith, honest and clean. An agreement is declared to have arisen when an agreement or agreement is reached between two parties regarding a main matter which is the object of the agreement. Agree here is defined as a conformity of understanding (opinion) and desires between two parties. In this context, there is a meeting of will between two parties to carry out or not carry out an agreement. This also applies to contracts (agreements) that are made electronically. In conventional society, an agreement is simply based on conformity of will. A meeting of wills requires the presence of both parties to agree on what has been agreed. Conformity of wishes can be done verbally or in writing. Then, in modern society which has utilized technology in its business activities, the agreement of wishes does not have to require a face-to-face meeting or the agreement does not have to be made in writing. This means that there is a shift in norms in society in interpreting conformity to will. In conventional society, of course, an agreement (conformity of will) must be made through a direct meeting to express a will. This is not the case in societies that have utilized technology. The emphasis in seeking agreement between the wishes of both parties is based on what one party states, then this statement is approved by the other party.